1987
DOI: 10.1002/micr.1920080106
|View full text |Cite
|
Sign up to set email alerts
|

Per‐operative topical administration of ZK 36 374 (iloprost) acts favorably on patency of small artery anastomoses in rats

Abstract: Aspirin (group I, 20 mg/kg, 0.5 hour preoperatively, ip, xylocaine (group II, topical administration of 1 ml of a 2% solution), and ZK 36,374 (Iloprost) either pre- or per- or postoperatively (group III, 10 micrograms/kg 0.5 hour peroperatively iv; group IV, topical administration of 1 ml of a solution containing 25 micrograms/ml peroperatively; and group V, 10 micrograms/kg 0.5 hour postoperatively iv) were given to groups of BN female rats in order to improve the patency rate of small artery (less than 0.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…37,93 The difference is only statistically significant when vein grafts were used. Illoprost, however, is less effective than systemic heparin at maintaining patency at sites of vein graft re-anastomosis.…”
Section: Dextranmentioning
confidence: 92%
See 1 more Smart Citation
“…37,93 The difference is only statistically significant when vein grafts were used. Illoprost, however, is less effective than systemic heparin at maintaining patency at sites of vein graft re-anastomosis.…”
Section: Dextranmentioning
confidence: 92%
“…In other studies systemic heparin provided greater protection against rethrombosis after the repair of a thrombosed anastomosis by vein graft repair than by simple re-anastomosis alone (82% vs 69% patency, respectively). 37 Stockmans et al 21 showed that heparin, when administered systemically to a therapeutic level (a 2-fold increase in PTT), reduces the rate of primary venous thrombosis by 60% whereas higher doses result in close to a 100% reduction. Higher plasma levels of heparin result in better protection against vascular thrombosis but increase the incidence of bleeding.…”
Section: Heparinmentioning
confidence: 98%
“…Other clinically available antithrombotic agents are iloprost, a synthetic analogue of prostacyclin (prostaglandin I 2 ) [56], hiruidin , which i s extracted from the saliva of leeches and can inactivate thrombin antithrombin III [27,57], and ketorolac, a nonsteroidal anti-inflammatory drug in the family of heterocyclic acetic acid derivatives that acts by inhibiting the body's synthesis of prostaglandins [58]. …”
Section: Pharmacological Interventionmentioning
confidence: 99%
“…L'aspirine représentait le traitement le plus employé. Expérimentalement, Salemark et al [13] retrouvaient une augmentation significative de la perméabilité artérielle en utilisant une dose faible (4 mg/kg) dix heures avant la chirurgie (niveau V expérimental) alors que Kort et al [14] n'en retrouvaient pas avec 20 mg/kg 30 minutes avant (niveau III expérimental). Les études cliniques en chirurgie cardiovasculaire [15] ne retrouvent pas de différence d'efficacité en termes de prévention de l'occlusion artérielle entre une administration Tableau 2 Protocole de prévention de la thrombose en microchirurgie retrouvés dans la littérature.…”
Section: Prévention Médicamenteuseunclassified